The Effect of Early Child Introduction to Pre-Vocational Subjects at the Primary School Level to Enhance Technological Growth in Developing Nations - Chamberlain, Ohwojero (Journal of Education and Vocational Research, 2015)
Technology is the power of development in many nations economy in this 21st century. Many developed nations in the western world have viable economy and strong technological background because of good educational foundation that was enhanced from the elementary stage of a child. Elementary education equips a child with good future background that will help to groom and prepare a child for future technological development and challenges. Nigeria as one of the developing countries in the world was used as a case study because of its poor educational background, which is the reason of this research on how to impart technological skills into children at the primary school level to enhance technological growth. To carry out this study three research questions were raised to guide the study with three hypotheses. All the primary schools in Nigeria were used as the population of the study. Questionnaire was the major instrument used for data collection. Data were analysed using mean and t-test analysis. Findings and recommendations were made to enhance the implementation of pre- vocational subjects in the developing Nations.